Accurate Understanding of the Letter of Lam Alif in Mushaf - WM, Al Hafiz; Mat Teh, Kamarul Shukri (RABBANICA - Journal of Revealed Knowledge, 2021)
Al - Qur’an is the holy book of the Muslims which is revealed in Arabic. Thus, every sentence, word and letter contained used is in Arabic. However, scholars have disagreed regarding the number and pronunciation of Arabic letters used in the Al - Quran. The same applies to the pronunciation of Lam Alif (لا), especially in the teaching and learning process. The purpose of this study is to examine the scholarly disagreement on this matter and to determine which is the correct pronunciation of the letter Lam Alif (لا). This study uses a qualitative approach through the design of content analysis studies. The study found that among the factors that led to the disagreement among scholars on the number of Hija’iyyah letters was to determine the letters Alif, whether it is classified as Hamzah, Alif Madd or not. These factors are also the origin of the letter Lam Alif and its pronunciation system. This study further reinforces the need for mastery in Arabic language especially involving Al - Quran such as the knowledge in Tajweed, and at the same time proving the importance of talaqqi and mushafahah in the teaching and learning process of Al - Quran.